NON-HIGH-DENSITY LIPOPROTEIN CHOLESTEROL VERSUS APOLIPOPROTEIN B AS PREDICTORS FOR CORONARY HEART DISEASE - AGGARWAL J.; SREENIVAS REDDY; SURYAKANT NAGTILAK (International Journal of Pharma and Bio Sciences, 2014)
Recently non high density lipoprotein cholesterol (non-HDL-C) and apolipoprotein B (apoB) have been found to be better and more reliable markers of atherosclerotic risk than LDL-C (low density lipoprotein cholesterol).Very few studies, as of now, are available in India which compared their predictability as a cardiovascular risk marker. The aim of our study was to evaluate and compare apoB and non-HDL-C and to find out the superiority of one over the other, if any. Lipid profile and apoB were determined in 110 subjects of coronary heart disease (CHD). Non-HDL-C was calculated. ApoB and non-HDL-C were compared in terms of receiver operating characteristic (ROC) curves. Within the constraints of this study there was statistically no difference between apoB and non-HDL-C in predicting CHD; therefore, this study supports the use of non-HDL-C as an initial screen for coronary risk as it incurs no additional cost, takes less time to report and is simple to calculate.